Sensory evaluation of pears: a useful tool to detect changes in eating quality during ripening - Raffo Benegas, Maria Dolores; Candan, Ana Paula; De Angelis, Veronica; Mañueco, María Lucía; Miranda, María José; Barda, Nora Beatriz (ISHS, 2025)
Trabajo presentado al XI International Pear Symposium, Argentina, 2010